Demand of electricity in China. - Chin, Chung Kong. (2008)
Developing countries like China are unable to meet the energy demands of their economies because of the shortage of adequate investment for new facilities to meet the demand growth. This study aims to investigate the impact of China's rapid economic development on the demand for electricity in the context of difficulties faced by China in developing its infrastructure. Subsequently, a forecast of China's electricity needs from 1998 to 2008 is attempted in this research.